Validation of patient determined disease steps (PDDS) scale scores in persons with multiple sclerosis - Learmonth, Yvonne C; Motl, Robert W; Sandroff, Brian M; Pula, John H; Cadavid, Diego (BMC neurology, 2013)
Background The Patient Determined Disease Steps (PDDS) is a promising patient-reported outcome (PRO) of disability in multiple sclerosis (MS). To date, there is limited evidence regarding the validity of PDDS scores, despite its sound conceptual development and broad inclusion in MS research. This study examined the validity of the PDDS based on (1) the association with Expanded Disability Status Scale (EDSS) scores and (2) the pattern of associations between PDDS and EDSS scores with Functional System (FS) scores as well as ambulatory and other outcomes. Methods 96 persons with MS provided demographic/clinical information, completed the PDDS and other PROs including the Multiple Sclerosis Walking Scale-12 (MSWS-12), and underwent a neurological examination for generating FS and EDSS scores. Participants completed assessments of cognition, ambulation including the 6-minute walk (6 MW), and wore an accelerometer during waking hours over seven days. Results There was a strong correlation between EDSS and PDDS scores ( ρ = .783). PDDS and EDSS scores were strongly correlated with Pyramidal ( ρ = .578 & ρ = .647, respectively) and Cerebellar ( ρ = .501 & ρ = .528, respectively) FS scores as well as 6 MW distance ( ρ = .704 & ρ = .805, respectively), MSWS-12 scores ( ρ = .801 & ρ = .729, respectively), and accelerometer steps/day ( ρ = -.740 & ρ = -.717, respectively). Conclusion This study provides novel evidence supporting the PDDS as valid PRO of disability in MS.